Socioeconomic Status Plays a Moderating Role in the Association Between Multimorbidity and Health-Related Quality of Life Among Cancer Patients - Xiao-Qing Ren MS; Shi-Jie Sun MS; Shen-Ao Wei MS; Shuo-Wen Fang MS; Ling-Feng Xu MS; Jian Xiao BS; Man-Man Lu PhD (SAGE Publishing, 2024)
This study aimed to explore the moderating role of socioeconomic status (SES) in the association between multimorbidity and health-related quality of life (HRQOL) among cancer patients in Anhui China. A total of 560 cancer patients were recruited for the cross-section study. Socio-demographic and clinical characteristics were analyzed using descriptive statistics. Tobit regression analysis was employed to investigate the relationship between multimorbidity and HRQOL as well as to assess the moderating effect of SES. The research findings indicated that 76.61% of cancer patients experienced multimorbidity, with psychological multimorbidity being the most prevalent (45.54%), followed by physical-psychological multimorbidity (20.89%). Moreover, physical-psychological multimorbidity had the most substantial adverse effect on HRQOL ( P < .001). The presence of multimorbidity was correlated with a significant decline in HRQOL, with a 17.5% ( P < .001) decrease in HRQOL for each additional multimorbidity. Additionally, SES played a significant role in moderating the impact of multimorbidity on HRQOL in cancer patients. (Marginal effect = −0.022, P < .01). The high SES group exhibited a higher overall HRQOL than the low SES group (Marginal effect = 0.068, P < .001). And with the increase of multimorbidity, HRQOL in the higher SES showed a more pronounced downward trend, compared with the lower SES ( β = −.270 vs β = −.201, P < .001). Our findings underscore the importance of preventing and managing multimorbidity in cancer patients, particularly those with low SES. Furthermore, it is essential to consider the impact of the rapid decline in HRQOL as the number of multimorbidity increases in individuals with higher SES. It is imperative to explore interdisciplinary and continuous collaborative management models.